Comprehensive phylogenomic analyses of ciliated protists with a revised classification of the phylum Ciliophora (Eukaryota, Alveolata) - Yurui Wang; Ying Yan; Zhenzhen Yi; Yan Zhao; Qianqian Zhang; Yong Chi; Tengyue Zhang; Weiwei Liu; Mingjian Liu; Borong Lu; Mingzhen Ma; Wenbao Zhuang; et al. (Science China Life Sciences, 2026)

Subchronic exposure of tire wear particles leachate induces oxidative stress and DNA damage in zebrafish (Danio rerio) brain - Bo Cheng; Yurui Hou; Yuqing Hou; Lanjun Wang; Yibo Gao; Yuhan Ye; Tao Tang; Baihui Shi; Junpu Wang; Lusheng Zhu; Jun Wang; Young Mo Kim; et al. (Journal of Environmental Management, 2026)

Current status of phylogenetic studies on ciliated protists (Alveolata, Protozoa, Ciliophora) by the OUC-group: advances, challenges and future perspectives - Feng Gao; Yang Bai; Yong Chi; Xiaochen Feng; Chunyu Lian; Borong Lu; Xiaotian Luo; Mingzhen Ma; Congcong Wang; Yurui Wang; Zhe Wang; Gongaote Zhang; et al. (Marine Life Science & Technology, 2025)
Ciliated protists (ciliates) represent a morphologically and genetically diverse group of single-celled eukaryotes, the phylogeny of which is critical for understanding eukaryotic evolution. Through international collaborations, the Laboratory of Protozoology at Ocean University of China (OUC-group) has conducted detailed research on ciliate phylogeny based on expanded taxonomic sampling, employing single gene as well as multi-gene markers, and phylogenomic datasets. We have systematically investigated > 1000 ciliate species spanning ~ 40 orders, sampled from diverse biotopes including marine environments in China seas and freshwater wetlands. This comprehensive sampling has generated three key datasets: (1) genomic DNA extracts from ~ 2600 strains, (2) ~ 2300 sequences of marker genes, and (3) single-cell genomic and/or transcriptomic datasets from ~ 120 species. Based on these datasets, the phylogenetic relationships covering all classes and most orders have been thoroughly reconstructed and investigated, resulting in the establishment of 93 new supraspecies taxa comprising two classes (Mesodiniea and Protocruziea), two subclasses (Protohypotrichia and Synhymenia), two orders (Wilbertomorphida and Lynnellida), 11 families, and 76 genera. Moreover, we have reconstructed a genome-scale tree of life for ciliates and provided an updated classification of the phylum Ciliophora. Furthermore, based on the robust phylogenetic tree of ciliates, we provide more reliable estimates for the origins and divergence times of the main ciliate groups. Future studies integrating advanced genomics, innovations in culturing and interdisciplinary applications will refine the ciliate tree of life, with broader impacts for our understanding of eukaryotic evolution and biodiversity.

Impacts of Qinling Mountains Elevation on Precipitation in Central China: A WRF Modelling Analysis - Bin Wang; Yiru Yang; Peter Clift; Wenting Gao; Li Xing; Yurui Zhang; Chris Brierley; Ting Sun; Hui Tang; Wei Shang; Ying Cheng; Shuangshuang Li; et al. (International Journal of Climatology, 2025)
The tectonically driven uplift of the Qinling Mountains during the Cenozoic may have resulted in significant climatic and environmental effects, but this remains poorly understood. This study investigates the influence of the Qinling Mountains' uplift on summer precipitation patterns in central China using the Weather Research and Forecasting (WRF) model to design topographic sensitivity experiments. The results show that the uplift of the Qinling Mountains leads to the intensification of the spatial distribution of precipitation in China, with increased precipitation in the south and decreased precipitation in the north. The uplift of the Qinling Mountains from an average elevation of 400 m to their current elevation results in a 13% (64.3 mm) decrease in precipitation north of the Qinling Mountains, a 39% (134.4 mm) increase in the Qinling Mountains, and a 1.5% (8.1 mm) increase to the south. In particular, precipitation in the Loess Plateau decreased by 62.7 mm (18%). As the Qinling Mountains uplift, the physical barrier effect is enhanced, leading to a reduction in water vapour over the Qinling Mountains. However, the forced uplift of air masses results in enhanced vertical motion, which in turn increases summer precipitation over the Qinling Mountains. In contrast, although water vapour accumulation occurs to the north of the Qinling Mountains, the absence of topographic forcing leads to decreased precipitation. When the Qinling Mountains uplifted to an average elevation of 1600 m, they began to exert a more pronounced blocking effect on wind and water vapour transport. This elevation effectively transformed the Qinling Mountains into a natural barrier, further separating the climatic regimes of the north and south of China. These findings indicate that the changes in elevation during the uplift of the Qinling Mountains have had a marked impact on the spatial distribution of precipitation in the central China.

Significantly enhanced piezoelectric properties of BaTiO3-based ceramics with unchanged curie temperature via local chemical inhomogeneity - Ming Wu; Ruifeng Yao; Chengyichang Jin; Yurui Xu; Jingzhe Xu; Liqiang He; Yang Yang; Yongbin Liu; Lisheng Zhong; Jinghui Gao (Chemical Engineering Journal, 2025)

Improved semi-infinite interval type-2 fuzzy multi-objective programming with integrated multi-criteria decision analysis for sustainable water resource management - Xi Zhang; Lei Jin; Yurui Fan; Li Wang; Jing Liu; Pangpang Gao (Journal of Water Process Engineering, 2025)

Effect of CFEM proteins on pathogenicity, patulin accumulation and host immunity of postharvest apple pathogens Penicillium expansum - Yanling Wang; Jie Gao; Xin Chen; Yanqi Huang; Yurui Wu; Jinfen Zhu; Wei Li (International Journal of Food Microbiology, 2025)

Extraction optimisation and compositional characterisation of total flavonoids from the Chinese herb tulip: a natural source of antioxidants and anti-inflammatory agents - Jiafeng Ye; Jiamin Cao; Xian Chen; Jingjing Ma; Yangchen Li; Xia Gao; Yurui Zhang; Chunli Wang (Natural Product Research, 2024)

Functional correlation tensors in brain white matter and the effects of normal aging - Lyuan Xu; Yurui Gao; Muwei Li; Richard Lawless; Yu Zhao; Kurt G. Schilling; Baxter P. Rogers; Adam W. Anderson; Zhaohua Ding; Bennett A. Landman; John C. Gore (Brain Imaging and Behavior, 2024)
Resting state correlations between blood oxygenation level dependent (BOLD) MRI signals from voxels in white matter (WM) are demonstrably anisotropic, so that functional correlation tensors (FCT) may be used to quantify the underlying microstructure of BOLD effects in WM tracts. However, the overall spatial distribution of FCTs and their metrics in specific populations has not yet been established, and the factors that affect their precise arrangements remain unclear. Changes in WM occur with normal aging, and these may be expected to affect FCTs. We hypothesized that FCTs exhibit a characteristic spatial pattern and may show systematic changes with aging or other factors. Here we report our analyses of the FCT characteristics of fMRI images of a large cohort of 461 cognitively normal subjects (190 females, 271 males) sourced from the Open Access Series of Imaging Studies (OASIS), with age distributions of 42 y/o – 95 y/o. Group averages and statistics of FCT indices, including axial functional correlations, radial functional correlations, mean functional correlations and fractional anisotropy, were quantified in WM bundles defined by the JHU ICBM-DTI-81 WM atlas. In addition, their variations with normal aging were examined. The results revealed a dimorphic distribution of changes in FCT metrics with age, with decreases of the functional correlations in some regions and increases in others. Supplementary analysis revealed that females exhibited significant age effects on a greater number of WM areas, but the interaction between age and sex was not significant. The findings demonstrate the reproducibility of the spatial distribution of FCT metrics and reveal subtle regional changes with age.

Development of a probabilistic agricultural drought forecasting (PADF) framework under climate change - Yizhuo Wen; Yifan Fei; Yurui Fan; Aili Yang; Bingqing Wang; PangPang Gao; Daniel Scott (Agricultural and Forest Meteorology, 2024)

Experimental study on environmental chemical effect and purification treatment of waste slurry in horizontal directional drilling - Pinghe Sun; YuRui He; Shengwei Zhou; Habiyakare Erneste; Qiang Gao; Zihao Zou; Junyi Zhu (Tunnelling and Underground Space Technology, 2024)

Development of chemical admixtures for green and environmentally friendly concrete: A review - Guanghong Lai; Xiao Liu; Shiyu Li; Yurui Xu; Yunsheng Zheng; Jianan Guan; Ruijun Gao; Zhongyuan Wei; Ziming Wang; Suping Cui (Journal of Cleaner Production, 2023)

Effect of Maize Straw Biochar on Bacterial Communities in Agricultural Soil - Jie Liu; Yanli Ding; Yurui Ji; Guanghai Gao; Yingying Wang (Bulletin of Environmental Contamination and Toxicology, 2020)

Further analyses of variation of ribosome DNA copy number and polymorphism in ciliates provide insights relevant to studies of both molecular ecology and phylogeny - Yurui Wang; Chundi Wang; Yaohan Jiang; Laura A. Katz; Feng Gao; Ying Yan (Science China Life Sciences, 2019)

A Web-Based Atlas Combining MRI and Histology of the Squirrel Monkey Brain - Kurt G. Schilling; Yurui Gao; Matthew Christian; Vaibhav Janve; Iwona Stepniewska; Bennett A. Landman; Adam W. Anderson (Neuroinformatics, 2019)

The VALiDATe29 MRI Based Multi-Channel Atlas of the Squirrel Monkey Brain - Kurt G. Schilling; Yurui Gao; Iwona Stepniewska; Tung-Lin Wu; Feng Wang; Bennett A. Landman; John C. Gore; Li Min Chen; Adam W. Anderson (Neuroinformatics, 2017)

Histone methyltransferase TXR1 is required for both H3 and H3.3 lysine 27 methylation in the well-known ciliated protist Tetrahymena thermophila - Xiaolu Zhao; Yuanyuan Wang; Yurui Wang; Yifan Liu; Shan Gao (Science China Life Sciences, 2017)

Enzymatic and chemical mapping of nucleosome distribution in purified micro- and macronuclei of the ciliated model organism, Tetrahymena thermophila - Xiao Chen; Shan Gao; Yifan Liu; Yuanyuan Wang; Yurui Wang; Weibo Song (Science China Life Sciences, 2016)